2012
DOI: 10.1152/ajpgi.00114.2011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin inhibits hepatocyte iNOS expression induced by cytokines by an Akt-dependent mechanism

Abstract: Harbrecht BG, Nweze I, Smith JW, Zhang B. Insulin inhibits hepatocyte iNOS expression induced by cytokines by an Akt-dependent mechanism. Am J Physiol Gastrointest Liver Physiol 302: G116-G122, 2012. First published October 28, 2011 doi:10.1152/ajpgi.00114.2011.-Hepatocyte inducible nitric oxide synthese (iNOS) expression is a tightly controlled pathway that mediates hepatic inflammation and hepatocyte injury in a variety of disease states. We have shown that cyclic adenosine monophosphate (cAMP) regulates cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…In line with the above observations, the inhibition of p38 MAPK also suppressed the expression of NF-κB, GATA4, and MEF2. Previous studies have shown that Akt activation caused cardiac hypertrophy in HFD feeding (Unsold et al, 2015, Zeidan et al, 2011, and SB203580 at a higher concentration not only influenced the p38 MAPK function, but also affected Akt function to certain degree (Harbrecht et al, 2012, Lali et al, 2000. However, in the present study, we found that Akt phosphorylation levels were not affected by SB203580, confirming that Akt signaling was not involve in the induction of pathological cardiac hypertrophy in HFD/obesity mice.…”
Section: Discussionmentioning
confidence: 96%
“…In line with the above observations, the inhibition of p38 MAPK also suppressed the expression of NF-κB, GATA4, and MEF2. Previous studies have shown that Akt activation caused cardiac hypertrophy in HFD feeding (Unsold et al, 2015, Zeidan et al, 2011, and SB203580 at a higher concentration not only influenced the p38 MAPK function, but also affected Akt function to certain degree (Harbrecht et al, 2012, Lali et al, 2000. However, in the present study, we found that Akt phosphorylation levels were not affected by SB203580, confirming that Akt signaling was not involve in the induction of pathological cardiac hypertrophy in HFD/obesity mice.…”
Section: Discussionmentioning
confidence: 96%
“…Hepatocyte viability was assessed using the 3-(4,5 dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (14). …”
Section: Methodsmentioning
confidence: 99%
“…RSV has been shown to activate several of these intracellular signaling pathways, including Akt (6, 8, 17). Since RSV activates Akt, and we know that Akt downregulates iNOS expression and activation (14, 15), we hypothesized that RSV would decrease inflammation-induced hepatocyte iNOS activation.…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability was measured using the 3-(4,5 dimethlythiazol-2-yl)-2,5-diphenyltetrazolium bromide assay (MTT) (25). After the indicated incubation, media was replaced with 5 mg MTT/ml in 70% ethanol diluted 1:50 with culture media, incubated for 30 minutes, removed, and 0.5 ml DMSO added.…”
Section: Methodsmentioning
confidence: 99%